Development and Performance Evaluation of an Embedded Magnetic Field Measurement System for River Sediment Monitoring - Megastin Massang Lumembang; Ferdy Ferdy; Berton M. Siahaan; Jorjie Abigael Sumanti; Geraldy J. C Pilat; Giovanny Paeh; Brian B. Mambu (Bulletin of Network Engineer and Informatics, 2026)
River sediment monitoring plays an important role in environmental and geophysical investigations, yet conventional magnetic characterization generally relies on laboratory-based instruments that are expensive, non-portable, and unsuitable for rapid field measurements. This study aimed to develop and evaluate an embedded magnetic field measurement system for river sediment monitoring using an HMC5883L magnetic sensor integrated with an Arduino Uno microcontroller. The developed system underwent performance evaluation under controlled laboratory conditions using a solenoid-generated magnetic field before being applied to river sediment samples collected from three different sampling locations. The performance evaluation was conducted at measurement distances of 1–7 cm, with three repeated measurements at each distance. The measured Z-axis magnetic field response decreased from 13.56 µT at 1 cm to -0.33 µT at 7 cm, and linear regression analysis yielded a coefficient of determination of R2 = 0.9632, indicating a consistent distance-dependent response within the evaluated range. The average magnetic field responses of the river sediment samples ranged from 54.5 µT to 245.6 µT across the three sampling locations, with a maximum difference of 197.7 µT. The developed embedded system provides a compact, portable, and low-cost platform for preliminary comparative assessment of magnetic field responses in river sediments. The measured values represent the sensor response obtained under the established experimental configuration and may include contributions from ambient magnetic fields; therefore, they should not be interpreted as direct measurements of the intrinsic magnetic properties or magnetic susceptibility of the sediment. The proposed system is intended for preliminary field screening and comparative magnetic response assessment, while quantitative characterization of magnetic minerals requires conventional laboratory-based magnetic measurement techniques